Shaping up for action: The path to physiological maturation in the renal tubules of Drosophila. - Denholm, B. (Organogenesis, 2013)
The Malpighian tubule is the main organ for excretion and osmoregulation in most insects. During a short period of embryonic development the tubules of Drosophila are shaped, undergo differentiation and become precisely positioned in the body cavity, so they become fully functional at the time of larval hatching a few hours later. In this review I explore three developmental events on the path to physiological maturation. First, I examine the molecular and cellular mechanisms that generate organ shape, focusing on the process of cell intercalation that drives tubule elongation, the roles of the cytoskeleton, the extracellular matrix and how intercalation is coordinated at the tissue level. Second, I look at the genetic networks that control the physiological differentiation of tubule cells and consider how distinctive physiological domains in the tubule are patterned. Finally, I explore how the organ is positioned within the body cavity and consider the relationship between organ position and function.